Piperacillin-Tazobactam (TZP) Resistance in Escherichia coli Due to Hyperproduction of TEM-1 β-Lactamase Mediated by the Promoter Pa/Pb - Zhou, Kaixin; Tao, Ying; Han, Lizhong; Ni, Yuxing; Sun, Jingyong (Frontiers in Microbiology, 2019)
TEM-1, mediated by plasmid and transposon, is the most commonly encountered β-lactamase in Gram -negative bacteria. Four different promoters upstream of blaTEM-related genes have been identified: the weak P3 promoter, and the strong promoters Pa/Pb, P4, and P5. In this study, we investigated the genetic basis of a clinical strain of E. coli (RJ904), which was found to be resistant to BLBLIs (β-lactam/β-lactamase inhibitors) , including amoxicillin-clavulanate, ticarcillin-clavulanate and piperacillin-tazobactam (TZP) but sensitive to third-generation cephalosporins. The conjugation test and S1-nuclease pulsed-field gel electrophoresis (S1-PFGE) demonstrated that transfer of this resistance was mediated by a ca. 100 kb plasmid . The transformant with TZP resistance was screened out with the shortgun cloning . Sequence analysis revealed that the recombinant plasmid contained a blaTEM-1b gene with the strong promoter Pa/Pb. Different plasmids were cloned based on the clone vector pACYC184 with the insertion of the blaTEM-1b gene with promoters Pa/Pb or P3. Susceptibility to TZP was determined by the Etest, agar dilution, and broth microdilution. The level of blaTEM-1b-specific transcription was determined by quantitative real-time PCR. Substitution of Pa/Pb for P3 resulted in a 128-fold decline of the MIC value of TZP, from >1024 mg/L to 8 mg/L, and a significantly lower blaTEM-1b expression level. Hyperproduction of TEM-1 β-lactamase mediated by the promoter Pa/Pb was responsible for high resistance to TZP in E. coli. Our data show possible risks of resistance development in association with the clinical use of TZP. The blaTEM promoter modifications should be considered for whole genome whole-genome sequencing-inferred bacterial antimicrobial susceptibility testing.